2018
DOI: 10.1186/s12888-018-1662-6
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of metabolic syndrome in patients receiving antipsychotics in Qatar: a cross sectional comparative study

Abstract: BackgroundMetabolic abnormalities are common in patients maintained on antipsychotics. These abnormalities increase the risk of cardiovascular diseases and mortality in this population. The aim of this study is to assess the prevalence of metabolic syndrome (MetS) in subjects maintained on antipsychotics relative to controls in Qatar, and to assess the factors contributing to the development of MetS.MethodsA cross sectional design was used to collect data and fasting blood samples from subjects maintained on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…It is challenging to control for all these confounders, but some studies attempted to look at the various demographic and clinical variables that might be associated with metabolic abnormalities. Such studies have shown that women tend to show more weight gain on AP (Bener et al 2014;Gates et al 2016;Santini et al 2016) than men but other studies showed mixed results in regard to gender (Hammoudeh et al 2018;Lin et al 2015;Susce et al 2005). Concerning ethnicity, a previous study from Qatar showed that non-Arabs were more prone to develop metabolic changes in the population of Qatar (Hammoudeh et al 2018), but other community studies worldwide showed no differences across race or ethnicity (Gates et al 2016;Phillips et al 2015).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…It is challenging to control for all these confounders, but some studies attempted to look at the various demographic and clinical variables that might be associated with metabolic abnormalities. Such studies have shown that women tend to show more weight gain on AP (Bener et al 2014;Gates et al 2016;Santini et al 2016) than men but other studies showed mixed results in regard to gender (Hammoudeh et al 2018;Lin et al 2015;Susce et al 2005). Concerning ethnicity, a previous study from Qatar showed that non-Arabs were more prone to develop metabolic changes in the population of Qatar (Hammoudeh et al 2018), but other community studies worldwide showed no differences across race or ethnicity (Gates et al 2016;Phillips et al 2015).…”
Section: Discussionmentioning
confidence: 98%
“…Concerning ethnicity, a previous study from Qatar showed that non-Arabs were more prone to develop metabolic changes in the population of Qatar (Hammoudeh et al 2018), but other community studies worldwide showed no differences across race or ethnicity (Gates et al 2016;Phillips et al 2015). Several studies have also demonstrated that older age, long duration of treatment, and smoking are associated with more metabolic changes in patients with mental illness and receiving AP (Hammoudeh et al 2018;Santini et al 2016;Sweileh et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the level of obesity (BMI) and glycemic control (HbA1c) was comparable between the two groups. A recent study in Qatar also found no difference in the prevalence of metabolic syndrome in patients receiving antipsychotics (9). The high prevalence of diabetes and obesity in the Qatar population could explain a lack of further effect of antipsychotics or schizophrenia on these outcomes (2, 3).…”
Section: Discussionmentioning
confidence: 99%
“…Nielsen et al showed that second generation antipsychotics were associated with an increased risk of diabetes (8). However, a study in Qatar did not nd a higher prevalence of metabolic syndrome in patients receiving antipsychotics (9). Dysglycemia is also associated with the severity of schizophrenia, particularly negative symptoms and cognitive impairment (10).…”
Section: Introductionmentioning
confidence: 99%